Forensic Accounting And Corporate Governance Maturity: Case Of Public Listed Companies In Oman - Rehman, Ali (2019)
Corporate governance maturity and forensic accounting can be considered as an essential component for the current business environment. Traditional audit activities have overlooked the role towards fraud detection which created expectation gaps; and due to this reason, inclusion of forensic accounting can be considered as an integral part in governance management system. In recent business environment, corporate governance system is becoming just a mere compliance check box tool; however, implementation of corporate governance maturity can overcome this traditional practice, as it defines how mature is the organization towards achievement of its goals, objectives and satisfied stakeholders. Thus present study developed a conceptual research framework for potential relationship between forensic accounting and corporate governance maturity. Research framework was developed in light of comprehensive literature review, observational study and expert opinions from academicians and professionals. Three management theories were applied namely agency theory for forensic accounting representing it as an agent, path dependence and convergence theory for corporate governance maturity as it defines structure and necessitated the required changes and fraud triangle theory for fraud risk assessment which is mediator in this study. Forensic accounting is independent variable and corporate governance maturity is dependent variable in this study. Forensic accounting is measured via its two dimensions namely preventive role and detective role, whereas corporate governance maturity is measured via its four major constituents namely board of director, audit and risk committee, remuneration committee and senior management.